DIGITAL CURRENCIES AND INTERNATIONAL TRADE: UNVEILING OPPORTUNITIES AND ADDRESSING CHALLENGES (World Bulletin of Social Sciences, 2025)
Traditional financial paradigms have changed due to the use of digital currencies in international trade. The study explores the intricate relationship between digital currencies and international trade, employing a multimodal research approach that integrates quantitative analysis and qualitative exploration. Drawing on data from Coinbase spanning the period 2013 to 2023, the study examines key variables such as transaction volumes, transaction speeds, and cost reductions to uncover underlying trends and patterns. Regression analysis reveals significant relationships between transaction volumes and transaction speeds, as well as transaction volumes and cost reductions. Correlation analysis confirms these associations, while Principal Component Analysis (PCA) provides insights into the underlying factors shaping the relationship. The findings highlight the transformative potential of digital currencies in reshaping global commerce, but also underscore the importance of informed risk management, technological innovation, and regulatory compliance efforts. While the study offers valuable insights into the evolving landscape of digital currencies and international trade, it acknowledges limitations such as the static nature of the dataset and the focus on macro-level influences. Future research could explore real-time dynamics, incorporate qualitative approaches, and examine social, cultural, and ethical dimensions of digital currency adoption. Overall, this study contributes to a deeper understanding of the complexities and challenges inherent in cross-border transactions involving digital currencies, informing strategies for stakeholders to harness the benefits while mitigating risks in a rapidly evolving global financial ecosystem